Therapeutic Effects of Stem Cells From Different Source on Renal Ischemia- Reperfusion Injury: A Systematic Review and Network Meta-analysis of Animal Studies - Shang, Zhizhong; Jiang, Yanbiao; Guan, Xin; Wang, Anan; Ma, Bin (Frontiers in Pharmacology, 2021)
Abstract Objective Although stem cell therapy for renal ischemia-reperfusion injury (RIRI) has made immense progress at the level of animal experiments, conflicting results have been reported by the investigators. Therefore, we aimed to systematically evaluate the effects of different stem cells on renal function in animals with ischemia-reperfusion injury and to compare the efficacies of stem cells from various sources. Methods PubMed, Web of Science, Embase, Cochrane, CNKI, VIP, CBM, and WanFang Data were searched for records until April 2021. Two researchers independently conducted literature screening, data extraction, and literature quality evaluation. Results and conclusion Seventy-two animal experiments were included in the data analysis. The results showed that stem cells from diverse sources could improve the renal function of RIRI animals. ADMSCs and MDMSCs were the most-researched stem cells, and they possibly hold the highest therapeutic potential. However, the quality of evidence included in this study is low, and there are many risks of bias. The exact efficacy of the stem cells and the requirement for further clinical studies remain unclear.